Evaluation of The Association of Lipid Profile With IL-6 Levels in an Acute Myocardial Infarction Scenario - Ahmed, Shaimaa Essa; Esmaeel, Omar Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Acute myocardial infarction (AMI) is a global health burden that targets the heart muscle and causes metabolic disorders as well as leads to increased inflammatory responses, and interleukin-6 (IL-6) is an axonal and anti-inflammatory cytokine that affects the stability of plaques, atherosclerosis, as well as endothelial damage, and cardiovascular outcomes. Therefore, the relationship between IL-6 and lipid disorders in AMI remains unclear, as it is in the Middle East community. This study aimed to clarify the levels of IL-6 in arterial tissue in patients with acute myocardial infarction and to examine their relationship with lipid parameters, fasting serum glucose, and signs of cardiac vitality. Several 30 cases including acute myocardial infarction were studied, which were admitted to the coronary care unit at Azadi Teaching Hospital since November 2024 and April 2025 with a matching health group according to sex, age, and measurement of lipid markers in arterial serum IL-6 Evidence of lipids (total cholesterol, triglycerides, HDL-C, LDL-C, and VLDL-C), fasting serum glucose, cardiac troponin I, and CK-MB B, By a program for biochemical and immunological statistical analysis. SPSS v25, using independent t-tests and Pearson correlation analysis, < 0.01 is statistically significant. The results showed that AMI patients showed an increase in serum IL-6, total cholesterol, triglycerides, LDL-C, VLDL-C, FASTING SERUM GLUCOSE, CK-MB, and cardiac troponin I in addition to a decrease in HDL-C compared to the two controls (p < 0.01). Serum IL-6 is strongly associated with fractions of atherogenic fats, fasting serum glucose, evidence of heart injury, and a negative association with HDL-C. High IL-6 levels are associated with fat decay, increased blood sugar, and their effect on the heart muscle and acute retention, characterizing the direct interaction between inflammation and metabolic disorders. IL-6 is a valuable biomarker for cardiovascular analysis and disease severity in AMI patients.